Temperature field measurement of an array of laminar premixed slot flame Jets using Mach-Zehnder interferometry. (May 2015) - Najafian Ashrafi, Z.; Ashjaee, M.
Abstract: An experimental study was performed to investigate the influence of Reynolds number (Re) and non-dimensional jet-to-jet spacing (S/Dh ) on flame shape, structure and temperature field of an array of laminar premixed slot flame jets. Mach-Zehnder interferometry technique is used to obtain an insight to the overall temperature field between single, twin and triple slot flame jets. The slot jets with large aspect ratio (L/W), length of L =60 mm and width of W =6 mm were used to eliminate the three-dimensional effect of temperature field. The effect of jet-to-jet spacing was investigated on flame characteristics under the test conditions of 200≤Re≤400 and equivalence ratio (φ) of unity. The present measurement reveals that the variation of maximum flame temperature with increment of Reynolds number is mainly due to heat transfer effects and is negligible while the flame height is increased. For the cases of twin and triple flame jets by increasing Reynolds number and decreasing non-dimensional jet-to-jet spacing (S/Dh ), the interferences between the jets are increased and the jets attracted each other. Strong interference was observed at S/Dh =1.15. For the case of triple jets at this S/Dh, the central jet was suppressed while the side jets deflected towards the inner jet. The interference between jets was found to reduce the heat flux in the jet-to-jet interacting zone due to incomplete combustion. Also the optimum jet-to-jet spacing of triple flame jets is obtained at each Reynolds number to enhance the heat transfer performance of the jets. Highlights: The height of the inner zone is augmented by increasing Reynolds number, but variation in maximum flame temperature is negligible. By reducing S/Dh, the multiple flame jets unify into one enlarged single flame jet, and this phenomenon reduced the thermal performance of the jets. The optimum jet-to-jet distances were obtained at S/Dh =2.29, 2.52 and 2.75 for Re=200, 300 and 400 respectively. For the twin slot flame jets by decreasing the jet-to-jet distance the heat flux is augmented while for the triple slot flame jets by reducing jet-to-jet spacing the central jet was suppressed, and the heat flux is decreased in this area.